1976
DOI: 10.1007/bf00277304
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic DNA repair in Escherichia coli

Abstract: The polC (= dnaE) temperature-sensitive DNA polymerase III mutation from Escherichia coli BT1026 has been transduced into E. coli WP2 (to give CM731) and WP2 uvr A (to give CM741). In excision-deficient CM741 UV-induced Trp+ mutations progressively lost their photoreversibility during post-irradiation incubation at 34 degrees. Immediately after transfer to 43 degrees, however, there was no further loss of reversibility although post-replication strand joining still occurred and uptake of 3H-thymidine into DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
31
0

Year Published

1978
1978
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(36 citation statements)
references
References 24 publications
5
31
0
Order By: Relevance
“…Echols had originally suggested that pol III core was a component of the mutasome, based primarily on genetic evidence indicating a requirement for pol III in SOS mutagenesis (27,28). We have found, however, that the presence of pol III core is not required for TLS (18,19), and in its presence pol V-catalyzed TLS is inhibited (19).…”
Section: Coping With Dna Damage In E Colimentioning
confidence: 74%
“…Echols had originally suggested that pol III core was a component of the mutasome, based primarily on genetic evidence indicating a requirement for pol III in SOS mutagenesis (27,28). We have found, however, that the presence of pol III core is not required for TLS (18,19), and in its presence pol V-catalyzed TLS is inhibited (19).…”
Section: Coping With Dna Damage In E Colimentioning
confidence: 74%
“…Also, it has been observed that a high cellular level of UmuC is exceptionally harmful to the defective DNA polymerase III (pol III) of the dnaQ49 mutant (38). These data suggest that UmuD and UmuC proteins may directly interact with the DNA replication apparatus.Experimental data available to date have suggested the involvement of DNA pol III in the SOS mutagenic pathway (4,17,23,40,41). Recent studies have shown that DNA pol III holoenzyme, in concert with UmuDЈ, UmuC, and RecA proteins, promotes in vitro replication across the site of the DNA lesion (21,40,41).…”
mentioning
confidence: 99%
“…1 and Table 1). Therefore, all we have learned about DNA synthesis by DNA polymerase I on irradiated template may also apply to DNA polymerase III,t which is more likely to be involved in UVinduced mutagenesis (28).…”
mentioning
confidence: 99%